2020
DOI: 10.3390/rs12030534
|View full text |Cite
|
Sign up to set email alerts
|

Inference in Supervised Spectral Classifiers for On-Board Hyperspectral Imaging: An Overview

Abstract: Machine learning techniques are widely used for pixel-wise classification of hyperspectral images. These methods can achieve high accuracy, but most of them are computationally intensive models. This poses a problem for their implementation in low-power and embedded systems intended for on-board processing, in which energy consumption and model size are as important as accuracy. With a focus on embedded and on-board systems (in which only the inference step is performed after an off-line training process), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 135 publications
(118 reference statements)
0
26
0
1
Order By: Relevance
“…We have decided to focus on GBDT instead of Random Forest since recently GBDT have demonstrated an enormous potential [5]. Moreover, [10] compared the results of Random Forest and GBDT and the results show that GBDT provided better accuracy while using smaller models, hence we believe that it is a better approach for embedded systems. Another difference is that we have designed a custom register-transfer level (RTL) architecture instead of using a high-level synthesis that will automatically generate the RTL design from a C-code.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We have decided to focus on GBDT instead of Random Forest since recently GBDT have demonstrated an enormous potential [5]. Moreover, [10] compared the results of Random Forest and GBDT and the results show that GBDT provided better accuracy while using smaller models, hence we believe that it is a better approach for embedded systems. Another difference is that we have designed a custom register-transfer level (RTL) architecture instead of using a high-level synthesis that will automatically generate the RTL design from a C-code.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, they have been successfully used to produce accurate forecasts for the COVID-19 evolution, and to identify factors that influence its transmission rate [6]; to detect fraud from customer transactions [7]; to estimate major air pollutants risks to human health [8] using satellite-based aerosol optical depth; or to classify the GPS signal reception in order to improve its accuracy [9]. Moreover, a recent publication [10] analyzed different machine learning methods for image processing in remote systems, focusing on on-board processing, which requires both performance and low-power. In this work the authors identified that GBDTs present a very interesting tradeoff between the use of computational and hardware resources and the obtained accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some widely used supervised classification approaches for HSI analysis are Multinomial Logistic Regression (MLR) [10], Support Vector Machine (SVM) [11], Maximum Likelihood [10,12], Ensemble Learning (EL) [13,14], Random Forests (RF) [15,16], Deep Learning (DL) [17][18][19], Transfer Learning [20,21], k-Nearest Neighbors (KNN) [22] and Extreme Learning Machine (ELM) [23]. The major limitation of supervised HSI classification is the poor performance due to the Hughes phenomena [24].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the data transmission from the remote-sensing platforms to the Earth surface introduces important delays related to the communication of a large amount of data between the source and the final target, producing a bottleneck that can seriously reduce the effectiveness of real-time applications or applications that demand prompt replies [21,22]. Consequently, real-time on-board processing has become a very interesting topic within the remote-sensing field to provide a solution to this type of applications [14,15,22,23]. In the space domain, this is due to the fact that both the acquisition rates of the next-generation hyperspectral sensors and the computational capabilities of the latest-generation space-grade hardware devices are growing [24].…”
Section: Introductionmentioning
confidence: 99%